HBW Special volume – new species and global index - Lambert, Frank (KUKILA, 2014)
Handbook of the Birds of the World. Special Volume: New Species and Global Index. . del Hoyo, J., Elliot, A., Sargatal, J. and Christie, D.A. (eds). 2013. Lynx Edicions, Barcelona. 812 pages, including 200 photos in the HBW Photo Gallery. ISBN-978-84-96553-88-0